(untitled) (Journal SCIENCEVOLUTION, 2024)
This research aims to examine the functioning of financial education in the management of personal finances among students at the Technical University of Machala, Ecuador, considering not only their financial decisions but also their spending habits. Likewise, it seeks to identify the socioeconomic factors that impact the level of financial education. The methodology employed is descriptive, documentary, deductive, and quantitative, using surveys applied to a sample of 373 students from various faculties. The results indicate that although the majority of students have received financial education, only a small percentage regularly apply this knowledge in their daily lives. Forty percent of the students acknowledge that their level of financial education influences their management of personal finances; however, there is a lack of saving habits and expense tracking. Furthermore, factors such as family influence, social environment, and income levels affect the development of financial skills. In conclusion, it is essential to strengthen financial education programs, promoting not only theoretical knowledge but also its practical application, in order to improve the economic stability and financial well-being of students.